Outcomes of Hepatitis C Virus Treatment in the New York City Jail Population: Successes and Challenges Facing Scale up of Care. (30th June 2020) - Chan, Justin; Schwartz, Jessie; Kaba, Fatos; Bocour, Angelica; Akiyama, Matthew J; Hobstetter, Laura; Rosner, Zachary; Winters, Ann; Yang, Patricia; MacDonald, Ross
Abstract: Background: The population detained in the New York City (NYC) jail system bears a high burden of hepatitis C virus (HCV) infection. Challenges to scaling up treatment include short and unpredictable lengths of stay. We report on the clinical outcomes of direct-acting antiviral (DAA) treatment delivered by NYC Health + Hospitals/Correctional Health Services in NYC jails from 2014 to 2017. Methods: We performed a retrospective observational cohort study of HCV patients with detectable HCV ribonucleic acid treated with DAA therapy while in NYC jails. Some patients initiated treatment in jail, whereas others initiated treatment in the community and were later incarcerated. Our primary outcome was sustained virologic response at 12 weeks (SVR12). Results: There were 269 patients included in our cohort, with 181 (67%) initiating treatment in jail and 88 (33%) continuing treatment started in the community. The SVR12 virologic outcome data were available for 195 (72%) individuals. Of these, 172 (88%) achieved SVR12. Patients who completed treatment in jail were more likely to achieve SVR12 relative to those who were released on treatment (adjusted risk ratio, 2.93; 95% confidence interval, 1.35–6.34). Of those who achieved SVR12, 114 (66%) had a subsequent viral load checked. We detected recurrent viremia in 18 (16%) of these individuals, which corresponded to 10.6 cases per 100 person-years of follow-up. Conclusions: Hepatitis C virus treatment with DAA therapy is effective in a jail environment. Future work should address challenges related to discharging patients while they are on treatment, loss to follow-up, and a high incidence of probable reinfection. Abstract : Treatment of hepatitis C virus (HCV) in the New York City jail system was effective, but challenges remain related to loss to follow-up and reinfection events. Patients discharged from jail while on treatment were less likely to achieve cure.